2016
DOI: 10.1111/tra.12393
|View full text |Cite
|
Sign up to set email alerts
|

Differential Use of the C‐Type Lectins L‐SIGN and DC‐SIGN for Phlebovirus Endocytosis

Abstract: Bunyaviruses represent a growing threat to humans and livestock globally. The receptors, cellular factors and endocytic pathways used by these emerging pathogens to infect cells remain largely unidentified and poorly characterized. DC-SIGN is a C-type lectin highly expressed on dermal dendritic cells that has been found to act as an authentic entry recep- The Bunyaviridae is a large family of RNA viruses, which comprises five genera (Hantavirus, Nairovirus, Orthobunyavirus, Phlebovirus and Tospovirus) (1). Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 49 publications
1
66
0
1
Order By: Relevance
“…Recent studies reveal that the lectin dendriticcell (DC) specific intercellular adhesion molecule 3-grabbing nonintegrin (SIGN) is identified as the entry factor required for many phleboviruses, including SFTSV, RVFV, Toscana virus (TOSV), and Uukuniemi virus (UU.K.V) (26,27). L-SIGN, another C-type lectin, shares 77% sequence homology with DC-SIGN and acts as an attachment receptor for these phleboviruses, rather than as an endocytic receptor (28). Nonmuscle myosin heavy chain II A (NMMHC-IIA) is reported as a critical factor contributing to the efficiency of early SFTSV infection, and the recombinant Gn protein is capable of binding NMMHC-IIA, indicating that Gn is likely the key receptor-binding protein (26).…”
Section: Significancementioning
confidence: 99%
“…Recent studies reveal that the lectin dendriticcell (DC) specific intercellular adhesion molecule 3-grabbing nonintegrin (SIGN) is identified as the entry factor required for many phleboviruses, including SFTSV, RVFV, Toscana virus (TOSV), and Uukuniemi virus (UU.K.V) (26,27). L-SIGN, another C-type lectin, shares 77% sequence homology with DC-SIGN and acts as an attachment receptor for these phleboviruses, rather than as an endocytic receptor (28). Nonmuscle myosin heavy chain II A (NMMHC-IIA) is reported as a critical factor contributing to the efficiency of early SFTSV infection, and the recombinant Gn protein is capable of binding NMMHC-IIA, indicating that Gn is likely the key receptor-binding protein (26).…”
Section: Significancementioning
confidence: 99%
“…dissected the differences in the interactions of phleboviruses, including Rift Valley fever virus (RVFV), Toscana virus, and Uukuniemi virus with DC-SIGN and L-SIGN [72]. In this study, an endocytosis-defective mutant of L-SIGN was still capable of facilitating viral infection, highlighting the role of L-SIGN as an attachment factor for phlebobviruses, whereas DC-SIGN acted as an authentic entry receptor [72]. Another study indicated DC-SIGN and L-SIGN as authentic endocytic receptors for influenza A virus (IAV) entry and infection [73].…”
Section: Myeloid C-type Lectins Receptors—pattern Recognition Recementioning
confidence: 99%
“…DC-SIGN acts as an endocytic receptor because it promotes viral internalization into endosomes. In contrast, L-SIGN, which shares 77% amino acid identity with DC-SIGN but is expressed in different cell types, promotes viral attachment but not viral uptake into cells (Leger et al, 2016), and is therefore considered an attachment factor only. Many other attachment factors have been identified for phleboviruses, such as heparan sulfate proteoglycans (de Boer et al, 2012;Riblett et al, 2015) and nonmuscle myosin heavy chain IIA (NMMHC-IIA) (Sun et al, 2014).…”
Section: Bunyavirus Entry Into Cellsmentioning
confidence: 99%